Pengaruh Motivasi, Minat Dan Kecerdasan Emosional Terhadap Prestasi Belajar Mahasiswa Semester VI di Akademi Keperawatan Dharma Husada - Hengki Irawan (coba, 2016)
Introduction : Learn to represent very basal element in management each, every education ladder and type. Efficacy of school activity can be seen from attainment of achievement learn reachedly. The aim of this research is to identify the influence between motivation, interest, and emotional intellegence with achievement learn semester student of VI Nursing Academy Of Dharma Husada Kediri. Desain Research is quantitative with cross sectional approach. The study was held on December, 2012 at Nursing Academy Of Dharma Husada Kediri. Variables in this study were Motivation, Interest and Emotional Intellegence as independent variables, and the Achievement him Learnas dependent variable. Population in this research was all VI semester student, andsample size was 82 persons. Sampling technique used was total sampling. Data was being collected by questionnaire and index to cumulative achievement. Data Analyzed by using double Linear regression test. Result of of study was the influence of motivation, interest and emotional intellegence to achievement learn with coefficient value of regresi 0.02 and 0.01 (t=5.987 and 4.334, interest do not have an effect on by signifikan to achievement learn with coefficient of regresi 0.03 ( test of t 0. 064) so that can be concluded that there are influence betwee motivation, interest and emotional intellegence to achievement learn with value of R2 = 0.696 and F Value = 93.800 significant = 0.000 < its 0.05 meaning equal to 69.6% achievement variation of learn to be explained by motivation variable, emotional intellegence and interest, the rest 30.4% determined by other factor and by simultan motivation variable, emotional intellegence and enthusiasm can explain achievement learn student. Conclusion According to research, there is significant betwenit the influence of motivation, interest and emotional intellegence to achievement learn.It is suggested to educator to increase ability teach it and risk motivation, interest and emotional intellegence and suggested for futher research on exploring physic and Phisicologist factor related/influence the achievement learn student.